Tentoonstelling van Moppes, Albert Cuypstraat. Geopend maart 1955. Midden: Mug. Links: burgemeester d'Ailly (1955)
Tentoonstelling van Moppes, Albert Cuypstraat. Geopend maart 1955. Midden: Mug. Links: burgemeester d'Ailly.